Conceptual model of land use administration in warfare: challenges, solutions and prospects for recovery - Dorosh, A.; Svyrydov, O. (Land Management, Cadastre and Land Monitoring, 2025)
The article examines key aspects of land use administration in conditions of military operations and the challenges facing local governments, state and military structures in terms of land resource management, as well as the prospects for land restoration after the end of hostilities. A conceptual model that encompasses legal, informational and organizational mechanisms for ensuring effective land management, protecting the rights of land owners, planning for territorial development, protectionism of individual territories to protect strategically important or vulnerable territories from uncontrolled use of resources, destruction or other threats aimed at protecting individual regions or territories from external influences, controlling strategically important territories and restoring land potential after the end of the conflict is proposed. The paper focuses on the importance of integrating digital information from the state land cadastre to identify the boundaries of occupied or liberated territories and adapting the legal framework to martial law conditions. The need for coordination between military, civilian, and international actors to ensure effective land administration in wartime and post-war recovery is discussed. The model offers a balanced approach to territorial development and long-term sustainability of land management, focused on sustainable development after the end of hostilities.Key words: land use administration, land cadastre, martial law, land restoration, legal regulation, information systems integration, territorial management, strategic resources, land management.
Keywords: land use administration; land cadastre; martial law; land restoration; legal regulation; information systems integration; territorial management; strategic resources; land management